IMPROVEMENT OF PUBLIC SERVICES IN IMMIGRATION THROUGH TECHNOLOGY BASED INNOVATION IN PASSPORT DELIVERY WITH GOJEK AS PARTNERS IN IMMIGRATION OFFICE CLASS I TPI SURAKARTA - Rangga Arya Mahendra (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
Gojek is one of the most popular online transportation companies today. The ability to provide various types of services to consumers as well as the guarantee of accountability for answers made Gojek often unable to cooperate with various government agencies. One of Gojek's popular services is Go Send. Go Send is a delivery service using the Gojek application. The Directorate General of Immigration always strives to continue to improve public services in the immigration sector, especially in terms of passport services carried out at the Immigration Office. Departing from these conditions, the author has the aim of making innovations in order to improve public services in the field of immigration, especially in terms of sending passports through the cooperation of the Immigration Office with Gojek. The problems that will be investigated are related to the legal basis and urgency of the possibility of future collaboration between the Class I TPI Surakarta Immigration Office and Gojek as well as what kind of passport delivery scheme can be done with Gojek. So that based on the results of the research that has been done, it can be denied that the cooperation between the immigration office and Gojek is very possible to be realized.